The MRI-Visible Nanocomposite Facilitates the Delivery and Tracking of siRNA Loaded DC Vaccine in the Breast Cancer Model - Wu, Changqiang; Zhu, Wencheng; Jin, Rongrong; Ai, Hua; Xu, Ye (Frontiers in Oncology, 2021)
Dendritic cell (DC) vaccines have recently been developed for the treatment of various cancers but often do not function as well as expected, primarily due to the highly complex in vivo immune environment. This proof-of-principle study aimed to test the feasibility of modulating the in vivo behaviors of DC vaccines (DCVs) by introducing siRNA-laden magnetic resonance (MR) imaging nanovectors into cells, while providing visible information on their homing to lymph nodes. The N-alkyl-PEI2k-LAC/SPIO nanocomposites were prepared and characterized, showing favorable properties of siRNA transfection and MRI labeling efficiency in DCs. Cell viability assays revealed no observable effects on the survival and phenotype of DCs if the concentration of the complex was within 8 μg Fe/ml. An orthotopic mouse model of breast cancer was developed. The DCVs transfected with IDO siRNA contained nanocomposites were adoptively transferred to start the treatment. MR imaging clearly visualized the homing of DCVs into lymph nodes. At the end of the treatment, DCVs presented significantly better tumor suppression than DCs or PBS (P < 0.05). Generally, the N-alkyl-PEI2k-LAC/SPIO nanocomposites represent a highly efficient MR imaging platform for siRNA transfection that is potentially useful for in vivo tracking of vaccine cells.